Soul's Platonic concept in Galenic work Soul faculties follow body temperaments - Hernández Artigas, Aniol (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2020)
In this paper we select the Platonic quotations about soul which Galen shows in his work Soul faculties follow body temperaments. Thereby, we analyze the soul galenic conception, which is the result of influence by divers medical-philosophical doctrines. Thus, considering human being has got three souls (rational, irascible and concupiscible) that are located in different parts and exercise various functions, Galen will diagnose and treat the soul diseases (passions and errors). So food, education and ambience influence human health, which will be harmonized psychophysically with diet, a complete treatment that will be a fundamental advance for the history of medicine.